Plantas, fertilizantes y transición energética en la caficultura contemporánea de Costa Rica. Bases para una discusión - López López, Maximiliano (2012)
This article analyzes the process of technological change in coffee farming in Costa Rica since 1950, focusing on the process of changing varieties in plantations throughout the period and its relation to the increased use of chemical fertilizers and other inputs of origin industrial. The assumption is that the inclusion of low height varieties such as Caturra, which allowed the expansion of coffee production to steep hills regions outside the Central Valley, demanded an increase in energy imports to the agroecosystems. The analysis is based on a review of documents from the era agronomic, agronomical mimeographed materials, interviews and reports from the Ministry of Agriculture and Livestock, IICA and ICAFÉ, among others.